Annual report of the West African Cocoa Research Institute of Nigeria - Cocoa Research Institute of Nigeria (Ibadan : Cocoa Research Institute of Nigeria, 1964)
This annual report is a comprehensive list of various research findings used in the development of cocoa in African countries.
Includes bibliographical references.
asm 04/03/2019
Ref
Keywords: Cocoa; Nigeria